Arthrogenic muscle inhibition and return to sport after arthrofibrosis complicating anterior cruciate ligament surgery. Issue 4 (3rd April 2022) - Dauty, Marc; Menu, Pierre; Mesland, Olivier; Fouasson-Chailloux, Alban
ABSTRACT: Arthrofibrosis is a devastating complication after Anterior Cruciate Ligament reconstruction (ACLr) characterized by a muscle weakness secondary to an arthrogenic muscle inhibition process. The loss of knee isokinetic strength due to arthrogenic muscle inhibition may be more important after arthrofibrosis, compared to an ACLr population with no complication. The isokinetic strength deficit [Limb Symmetry Index (LSI) at 60 and 180°/s of angular speed] was measured at 4, 7 and 12 post-operative months. Knee function, return to running and return to sport were evaluated. A comparison of the Quadriceps and the Hamstring LSI between patients with arthrofibrosis and those without post-operative complication was performed according to time and taking into consideration the type of surgical procedure. 539 primary ACLr patients were assessed. The arthrofibrosis group presented at 4, 7 and 12 post-operative months a Quadriceps LSI significantly lower compared to the control group, without influence of the graft procedure (LSI: 38, 53, 68% vs 63, 73, 85% at 60°/s, respectively). The Hamstring LSI was significantly lower at 4 and 7 post-operative months, but comparable at 12 months with an influence of the Hamstring procedure. Knee function was significantly lower at 4 and 7 post-operative months. Few arthrofibrosis ACLr patients returned to running at 7 post-operative months (6.8% vs 69.9%; p  < .0001). An important and durable Quadriceps muscle weakness occurred after arthrofibrosis, whatever the type of graft procedure. This is explained by an Arthrogenic muscle inhibition which compromised the return to sport at the same level until 12 post-operative months. Highlights An important and durable quadriceps muscle weakness occurred after arthrofibrosis. The arthrogenic muscle inhibition was significant on the operated side independently of the type of the graft procedure. Arthrogenic muscle inhibition compromised the return to sport at the same level until 12 post-operative months.